The impact of the COVID-19 pandemic on dental trauma attendance: a systematic review and meta-analysis - Débora e Silva CAMPOS; Isis de Araújo Ferreira MUNIZ; Amanda Claudino GOMES; Letícia Regina Marques BESERRA; Luyra Elyka Daniel dos SANTOS; André Ulisses Dantas BATISTA; Luciana Ferraz GOMINHO; Juan Ramon SALAZAR-SILVA; Fábio Luiz Cunha D'ASSUNÇÃO (University of São Paulo, 2023)
Abstract This systematic review and meta-analysis aimed to analyze the impact of the COVID-19 pandemic on dental trauma patient attendance. The study was registered in the PROSPERO system, using the CRD42021288398 protocol. Searching was performed in PubMed, Scopus, Web of Science, Embase, Lilacs, and OpenGrey databases, using the following keywords: "Tooth injuries," "Dental trauma," "Traumatic Dental injury," and "COVID-19". We included observational studies evaluating dental trauma in the context of the COVID-19 pandemic. Quality assessment was performed using the Joanna Briggs Institute Critical Appraisal Checklist for Cross-Sectional Studies. Meta-analysis was performed in RevMan 5.4 software with Odds Ratios as a pooled measure of effect, with a 95% confidence interval, and using random-effects modeling. After applying the eligibility criteria, 32 studies were included for qualitative analysis, in which 10 were used to assess the frequency of dental trauma diagnoses in dental emergencies. Despite the decrease of visits during COVID-19, the analysis revealed no difference between the pandemic and pre-pandemic periods. Regarding the type of dental trauma, two of the studies revealed no differences for the periods before and during the pandemic. This study revealed that the COVID-19 pandemic has not impacted the frequency or type of dental trauma compared to previous periods.